2007
DOI: 10.1590/s0100-879x2006005000055
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells from patients with chronic myeloid leukemia do not express BCR-ABL and have absence of chimerism after allogeneic bone marrow transplant

Abstract: Bone marrow is a heterogeneous cell population which includes hematopoietic and mesenchymal progenitor cells. Dysregulated hematopoiesis occurs in chronic myelogenous leukemia (CML), being caused at least in part by abnormalities in the hematopoietic progenitors. However, the role of mesenchymal stem cells (MSCs) in CML has not been well characterized. The objectives of the present study were to observe the biological characteristics of MSCs from CML patients and to determine if MSCs originate in part from don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
2
2
0
1
Order By: Relevance
“…We further assessed these stem cells for presence or absence of BCR/ABL transcript and we found that cells isolated and grown from CML patients were BCR/ABL -ve cells and therefore we designated these cells as BCR/ABL -ve cell line. A similar study was carried out by Carrara et al [17] and our results are obtained in concordance with them. Upon establishment of the BCR/ABL -ve cell line and thorough observation of phenotypic characters through phase contrast microscopy and Giemsa staining, we could taper down to the idea of presence of mesenchymal stem cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We further assessed these stem cells for presence or absence of BCR/ABL transcript and we found that cells isolated and grown from CML patients were BCR/ABL -ve cells and therefore we designated these cells as BCR/ABL -ve cell line. A similar study was carried out by Carrara et al [17] and our results are obtained in concordance with them. Upon establishment of the BCR/ABL -ve cell line and thorough observation of phenotypic characters through phase contrast microscopy and Giemsa staining, we could taper down to the idea of presence of mesenchymal stem cells.…”
Section: Discussionsupporting
confidence: 93%
“…The data collected through these experiments suggest that the cells are likely normal and do not seem to be obnoxious in any way though derived from a patient in blast crisis of CML. These results of attaining normal MSCs are in concordance with previous studies which have reported isolation of normal MSCs from CML patients [17]. Many studies have pointed towards the use of MSCs in treating CML.…”
Section: Discussionsupporting
confidence: 92%
“…The role of tumor-derived exosomes in tumor niche dysfunction is complex, and they can participate in homing, niche-immune responses, angiogenesis, tumor cell growth, and immunosuppression (Whiteside, 2016). As per our knowledge, the functional properties and secretome of MSC are altered in the leukemic bone marrow (Carrara et al, 2007, Geyh et al, 2016, López et al, 2014. We hypothesized that CML-derived exosomes have a critical role in creating inflammatory and tumor-favorable local condition in BM-MSCs and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated MSCs from the BM of patients with chronic myeloid leukemia did not demonstrate any presence of the Philadelphia chromosome, retained their ability to differentiate into osteoblasts and could support expansion of cord blood stem cells (Jootar et al 2006). MSCs from patients with chronic myeloid leukemia expressed the typical MSCs phenotype and differentiated into osteogenic and adipogenic lineages (Carrara et al 2007). The supposition of the risk that MSCs after the in vitro cultivation prepared for application to the patient would be contaminated by hematopoietic cells is low, since cultures of human MSCs become free of hematopoietic precursors after one or two passages (Sekiya et al 2002) and according to our experiences they are washed out after the first cultivation medium exchange after the seeding.…”
Section: Discussionmentioning
confidence: 99%